BE_ZIVILSTRAF BK 2018 500 vom 9. Mai 2019 - BE Obergericht (2019)
Einstellung/Ausstand; Strafverfahren wegen Betrugs, falscher Anschuldigung, Verleumdung und Beschimpfung | Einstellung/Nichtanhandnahme